Lipid interactions of an actinoporin pore-forming oligomer - Sepehri, Aliasghar (Biophys J, 2021)
The actinoporins are cytolytic toxins produced by sea anemones. Upon encountering a membrane, preferably containing sphingomyelin, they oligomerize and insert their N-terminal helix into the membrane, forming a pore. Whether sphingomyelin is specifically recognized by the protein or simply induces phase coexistence in the membrane has been debated. Here, we perform multi-microsecond molecular dynamics simulations of an octamer of fragaceatoxin C, a member of the actinoporin family, in lipid bilayers containing either pure 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) or a 1:1 mixture of DOPC and palmitoyl sphingomyelin (PSM). The complex is highly stable in both environments, with only slight fraying of the inserted helices near their N-termini. Analyzing the structural parameters of the mixed membrane in the course of the simulation, we see signs of a phase transition for PSM in the inner leaflet of the bilayer. In both leaflets, cross-interactions between lipids of different type decrease over time. Surprisingly, the aromatic loop thought to be responsible for sphingomyelin recognition interacts more with DOPC than PSM by the end of the simulation. These results support the notion that the key membrane property that actinoporins recognize is lipid phase coexistence.